Campaign finance and perceptions of interest group influence in Australia. (4th May 2018) - Cameron, Sarah; Wynter, Thomas
ABSTRACT: Comparative studies routinely demonstrate that Australia underperforms relative to other established democracies on measures of campaign finance integrity and the role of money in politics. Scandals relating to the influence of political donations have affected both major parties in recent elections, and record numbers of Australians believe that the government is run for a few big interests. Previous studies have focused on the problems of Australian political financing arrangements, and reforms at the state level, but little is known about public perceptions of the influence of money in politics in Australia. This paper examines these perceptions with data from the Australian Election Study covering elections from 1990 to 2016. Using multilevel modelling we investigate the role of election level and individual level characteristics on perceptions of the influence of major interest groups in Australian politics. We find that when the Liberal-National Coalition is in government, there is greater concern over the role of big interests in politics. At the individual level, we find that partisanship, ideology, being an electoral winner or loser, and economic evaluations affect citizens' perceptions of interest group influence.